IT Governance – An International Guide to Data Security and ISO 27001/ISO 27002 (8th Edition) - Calder, Alan; Watkins, Steve (IT Governance Publishing, 2024)
In this updated edition, renowned ISO 27001/27002 experts Alan Calder and Steve Watkins:* Discuss the ISO 27001/27002:2022 updates;* Provide guidance on how to establish a strong IT governance system and an ISMS (information security management system) that complies with ISO 27001 and ISO 27002;* Highlight why data protection and information security are vital in our ever-changing online and physical environments;* Reflect on changes to international legislation, e.g. the GDPR (General Data Protection Regulation); and* Review key topics such as risk assessment, asset management, controls, security, supplier relationships and compliance.